PENGARUH SELF ASSESSMENT SYSTEM TERHADAP PENERIMAAN PPN PADA PENGUSAHA KENA PAJAK DI KPP PRATAMA SEMARANG BARAT - Adimas Kuswandoko, 09.05.52.0001; Setyowati, Widhy (Students Journal of Accounting and Banking, 2013)
This research aims to examine the influence of number variable of PKP registered, SSP PPN deposited, SPT massa PPN reported, and SPT PPN published to the inflow of PPN in KPP PRATAMA West Semarang in the period 2008 until 2012 simultaneously and partially. The sample in this research are number PKP, SSP, SPT massa PPN, STP PPN in KPP PRATAMA West Semarang in the period 2008 until 2012 or for 60 months. Kinds of data used in this research is secondary data. An instument analysis used in this research is multiple linier regression. The result of the research shows that number of PKP registered (X1) and number of SSP PPN deposited (X2) have a significant positive to the inflow of PPN (Y), while number of SPT massa PPN reported(X3) has a significant positive. Furthermore, amount of STP PPN published (X4) has a no significant positive to the inflow of PPN (Y).Keywords: Self assesment system, PKP, SSP PPN, SPT massa PPN,STP PPN, PPN